Assessing Terrorist Cyber-Risks and the Potential Use of Terrorist Cyber-Threats in the Maritime Sector - Γκουσγκούνης, Γεώργιος (Πανεπιστήμιο Πελοποννήσου, 2016)
September 11, 2001, made clear that terrorists have the ability to use unconventional means for their attacks. Terrorists’ strategy started shifting towards economic targets and proved that ordinary means of transportation can be transformed into lethal weapons. Since September 11, 2001 worries have arisen within the maritime sector about the possibility for terrorist actions against ships, and port facilities by terrorists using ships as weapons approximately in the same way as airplanes were used as weapons. There have been fears that the terrorists might make use of piracy sea tactics to achieve successful attacks at sea. However, delivering attacks in the maritime environment presents many problems. The main worries for all the stakeholders then shifted to a potential tactical nexus between piracy and terrorism. Nevertheless, there is no evidence that pirates and terrorists have a collusion or that they will because there exists a very thin line between them. Consequently, terrorists are trying to advance their methods in order to achieve their goals by overcoming these barriers. Therefore, terrorists adjust their tactics, modus operandi and sometimes even their weapon systems and exploit the dependence of commerce and communication on electronic means so as to accomplish their efforts. Recent recorded cases of successful cyber-attacks require the sector’s full attention. The aim of this dissertation is to identify the main problems in the maritime sector, describe the methods that terrorists use for their purposes and perform a risk analysis to map out potential threat scenarios that involve cyber-attacks to ships and critical maritime infrastructures.
Αξιολόγηση Τρομοκρατικών Κυβερνό-κινδύνων και η εν Δυνάμει Χρήση Τρομοκρατικών Κυβερνο- απειλών στη Ναυτιλία
Keywords: Τρομοκρατία; Πειρατεία πλοίων; Διαχείριση κινδύνου; Τρομοκρατία; Ναυτιλία; Πειρατεία; Ανάλυση κινδύνου; Κυβερνο-Απειλές